Relationship Between Employee Value Proposition and Resignation with The Moderating Effect of Employee Satisfaction - Fakhri, Muhammad Shidqi; Saragih, Eva Hotnaidah; Dwiyana, Annisa (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2023)
COVID-19 pandemic brought concerns to the corporation with the great resignation phenomenon that happens around the world, especially in developed nations. Workers now have different views after the pandemic, where they view well-being as an important aspect of work and employee value proposition. Therefore it is important to know how Indonesians view this issue. The method of this study is an electronic survey with respondents which are workers around Jabodetabek metropolitan areas, with a range of age between 26-35 years. Surveys are based on three variables, employee value proposition (Idv), intention to resign (Dv), and employee satisfaction (M). Results then analyzed with moderated regression analysis and linear regression analysis, to view the validity of the hypotheses. This research found: (1) employee value proposition significantly has a negative influence on intention to resign, and (2) the relationship between employee value proposition and intention to resign significantly are not moderated by employee satisfaction. Corporations in Indonesia need to search for other means to maintain their employee commitment, as employee satisfaction only approaches by behaviorally influencing its employees. Different approaches like revising company EVP that is based on the right valence need to be done to satisfy and maintain commitment of Indonesian workers.